Acute Effects of the New Method Sarcoplasma Stimulating Training Versus Traditional Resistance Training on Total Training Volume, Lactate and Muscle Thickness - de Almeida, Fernando Noronha; Lopes, Charles Ricardo; Conceição, Raphael Machado da; Oenning, Luan; Crisp, Alex Harley; de Sousa, Nuno Manuel Frade; Trindade, Thiago Barbosa; Willardson, Jeffrey M.; Prestes, Jonato (Frontiers in Physiology, 2019)
Background: Trained subjects have difficulty in achieving continued results following years of training, and the manipulation of training variables through advanced resistance training (RT) methods is widely recommended to break through plateaus. Objective: The purpose of the present study was to compare the acute effects of traditional RT (TRT) versus two types of sarcoplasma stimulating training (SST) methods on total training volume (TTV), lactate, and muscle thickness (MT). Methods: Twelve trained males (20.75 ± 2.3 years; 1.76 ± 0.14 meters; body mass = 79.41 ± 4.6 kg; RT experience = 4.1 ± 1.8 years) completed three RT protocols in a randomly sequenced order: TRT, SST contraction type (SST-CT), or SST rest interval variable (SST-RIV) with 7 days between trials in arm curl (elbow flexors) and triceps pulley extension (elbow extensors) performed on the same day. Results: The SST groups displayed greater acute biceps and triceps brachii (TB) MT versus the TRT session, with no difference in lactate levels between them. The SST-CT resulted in greater biceps and TB MT versus the SST-RIV session. The TTV was greater for the TRT session versus the SST sessions, except in the case of the elbow flexors (no difference was observed between TRT and SST-CT), and higher for the SST-CT versus the SST-RIV. Conclusion: Trained subjects may benefit from using the SST method as this method may offer a superior MT stimulus and reduced training time, even with a lower TTV.